Primitive Sca-1 Positive Bone Marrow HSC in Mouse Model of Aplastic Anemia: A Comparative Study through Flowcytometric Analysis and Scanning Electron Microscopy - Sumanta Chatterjee; Pratima Basak; Prosun Das; Madhurima Das; Jacintha Archana Pereira; Ranjan Kumar Dutta; Malay Chaklader; Samaresh Chaudhuri; Sujata Law (Stem Cells International)
Self-renewing Hematopoietic Stem Cells (HSCs) are responsible for reconstitution of all blood cell lineages. Sca-1 is the “stem cell antigen” marker used to identify the primitive murine HSC population, the expression of which decreases upon differentiation to other mature cell types. Sca-1+ HSCs maintain the bone marrow stem cell pool throughout the life. Aplastic anemia is a disease considered to involve primary stem cell deficiency and is characterized by severe pancytopenia and a decline in healthy blood cell generation system. Studies conducted in our laboratory revealed that the primitive Sca-1+ BM-HSCs (bone marrow hematopoietic stem cell) are significantly affected in experimental Aplastic animals pretreated with chemotherapeutic drugs (Busulfan and Cyclophosphamide) and there is increased Caspase-3 activity with consecutive high Annexin-V positivity leading to premature apoptosis in the bone marrow hematopoietic stem cell population in Aplastic condition. The Sca-1bright, that is, “more primitive” BM-HSC population was more affected than the “less primitive” BM-HSC Sca-1dim⁡ population. The decreased cell population and the receptor expression were directly associated with an empty and deranged marrow microenvironment, which is evident from scanning electron microscopy (SEM). The above experimental evidences hint toward the manipulation of receptor expression for the benefit of cytotherapy by primitive stem cell population in Aplastic anemia cases.